Serum IL-1 β , IL-2, and IL-6 in Insulin-Dependent Diabetic Children (Mediators of Inflammation)
Insulin-dependent diabetes mellitus (IDDM) is a chronic disease characterized by T-cell-dependent autoimmune destruction of the insulin-producing β cells in the pancreatic islets of Langerhans, resulting in an absolute lack of insulin. T cells are activated in response to islet-dominant autoantigens, the result being the development of IDDM. Insulin is one of the islet autoantigens responsible for the activation of T-lymphocyte functions, inflammatory cytokine production, and development of IDDM. The aim of this study was to investigate serum concentrations of interleukin (IL)-1 β , IL-2, IL-6, and tumor necrosis factor (TNF)- α in children IDDM. The study population consisted of 27 children with IDDM and 25 healthy controls. Children with IDDM were divided into three subgroups: (1) previously diagnosed patients (long standing IDDM) ( n : 15 ), (2) newly diagnosed patients with diabetic ketoacidosis (before treatment) ( n : 12 ), and (3) newly diagnosed patients with diabetic ketoacidosis (after treatment for two weeks) ( n : 12 ). In all stages of diabetes higher levels of IL-1 β and TNF- α and lower levels of IL-2 and IL-6 were detected. Our data about elevated serum IL-1 β , TNF- α and decreased IL-2, IL-6 levels in newly diagnosed IDDM patients in comparison with longer standing cases supports an activation of systemic inflammatory process during early phases of IDDM which may be indicative of an ongoing β -cell destruction. Persistence of significant difference between the cases with IDDM monitored for a long time and controls in terms of IL-1 β , IL-2, IL-6, and TNF- α supports continuous activation during the late stages of diabetes.